2006
DOI: 10.1002/cjoc.200690160
|View full text |Cite
|
Sign up to set email alerts
|

MCM‐41 Bound Ruthenium Complex as Heterogeneous Catalyst for Hydrogenation I: Effect of Support, Ligand and Solvent on the Catalyst Performance

Abstract: The functionalized MCM-41 mesoporous bound ruthenium complex was synthesized and characterized using elemental analysis, atomic absorption spectrophotometer, BET, XRD and FTIR. Hydrogenation of carbon dioxide to formic acid was investigated over these catalysts under supercritical CO 2 condition. The effect of reactant gas partial pressure, supports, solvents and ligands on the synthesis of formic acid was studied. These factors could influence the catalyst activity, stability and reuse performance greatly and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…For example, over the first reaction cycle 8% of active metal leaching was indicated for the amine functionalized silica compared to the one functionalized with thiol (2.5% metal leaching) ascribed to the weaker complexation, but higher activity of the former. 79 Although in this case the Ru–H vibration was detected by FTIR, no characterization was reported for the spent catalyst. Rohr et al showed that multiple coordination using two bidentate ligands ( Figure 3 a) could greatly improve the stability of the catalyst by enhancing the binding strength to Ru compared to the cases where the active metal is weakly bound via a single coordination ( Figure 3 b).…”
Section: Direct Hydrogenation Of Co 2 To Formate/fmentioning
confidence: 84%
See 4 more Smart Citations
“…For example, over the first reaction cycle 8% of active metal leaching was indicated for the amine functionalized silica compared to the one functionalized with thiol (2.5% metal leaching) ascribed to the weaker complexation, but higher activity of the former. 79 Although in this case the Ru–H vibration was detected by FTIR, no characterization was reported for the spent catalyst. Rohr et al showed that multiple coordination using two bidentate ligands ( Figure 3 a) could greatly improve the stability of the catalyst by enhancing the binding strength to Ru compared to the cases where the active metal is weakly bound via a single coordination ( Figure 3 b).…”
Section: Direct Hydrogenation Of Co 2 To Formate/fmentioning
confidence: 84%
“…For example, over the first reaction cycle 8% of active metal leaching was indicated for the amine functionalized silica compared to the one functionalized with thiol (2.5% metal leaching) ascribed to the weaker complexation, but higher activity of the former. 79 Although in this case the Ru−H vibration was detected by FTIR, no characterization was reported for the spent catalyst. Rohr et al…”
Section: Chemical Reviewsmentioning
confidence: 86%
See 3 more Smart Citations